A review of the state-of-the-art on thermal insulation performance of polymeric foams. (1st June 2023) - Hasanzadeh, Rezgar; Azdast, Taher; Lee, Patrick C.; Park, Chul B.
Highlights: A comparative analysis was performed between the prevalent insulating materials. Comparative analysis was conducted using multi-criteria decision-making methods. Overall, polymeric foams were among the most talented thermal insulating materials. A theoretical model was developed to predict the overall thermal conductivity. The most valuable experimental achievements were reviewed. Abstract: Achieving the global energy sustainability plays a key role in the energy fields. Thermal insulation materials play a vital role on this sustainability. There are different potential thermal insulating materials such as cork, cellulose, mineral wools, vacuum insulation panels, aerogels and polymeric foams. Polymeric foams are one of the most promising thermal insulation materials with a bright outlook and widespread application range. In this review, a comparative analysis was performed using multi-criteria decision making methods between the prevalent insulating materials. It was concluded that the polymeric foams were the most promising thermal insulating materials for different applications. A theoretical model was developed using the literature data to predict the overall thermal conductivity based on the foam density and the cell size and was validated in comparison to the experimental results. The most valuable experimental achievements in the field of thermal insulation performance of the polymeric foams in recent years were reviewed.